The Influence Of Work Ability, Work Discipline, And Organizational Commitment To Performance Employees In PT Jne's Outbound Division Express Main Branch Medan - Ika Yulanda; Niken Wulandari; Emi Wakhyuni (Yayasan Multidimensi Kreatif, 2025)
The research analysis aims to find out whether work ability, work discipline and organizational commitment to employee performance. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This study uses multiple linear regression analysis. The sample in this study is 55 respondents. Primary data collection uses questionnaires. The results of the study showed that workability had a positive and partially significant effect on the performance of employees of the Out Bound Division of PT JNE Express. Work discipline has a positive and partially significant effect on the performance of employees of PT JNE Express's Out Bound Division. Organizational commitment does not have a significant partial effect on the performance of employees of PT JNE Express's Out Bound Division. Work ability, work discipline and organizational commitment have a positive and significant effect simultaneously on the performance of employees of PT JNE Express's Out Bound Division